Towards the development of guidelines for improving the sustainability of diets and food consumption patterns: the Mediterranean Diet as a pilot study - Capone R.; Lacirignola C.; Dernini S.; Meybeck A.; Burlingame B.; Gitz V.; El Bilali H.; Debs P.; Belsanti V. (Options Méditerranéennes : Série B. Etudes et Recherches, 2012)
This paper is the outcome of the collaboration between FAO and MAI Bari (CIHEAM). It was prepared for the session on "Food Systems and Sustainable Diets: The Mediterranean diet as a Pilot Study" of the International Seminar on "The Sustainability of Food Systems in the Mediterranean Area"; organised on the occasion of the 9th Meeting of the CIHEAM Ministers of Agriculture, held in September 2012 in Malta. This paper aims at contributing to the design of guidelines to improve the sustainability of diets and addressing the main challenges faced by food systems in the Mediterranean area. The paper (i) analyses the concept of sustainable diets as well as the main drivers of (un)sustainable food consumption and production; (ii) discusses the main nutritional, health, economic, environmental and socio-cultural challenges related to food consumption patterns in Mediterranean countries; (iii) proposes a preliminary methodological framework for the assessment of the sustainability of the Mediterranean diets especially some tentative indicators; and (vi) presents future joint research and action programmes/projects for enhancing the Mediterranean diets sustainability.
The Sustainability of Food Systems in the Mediterranean Area, 2012/09/25-26, Valetta (Malta)